Ruptured Left Ovarian Teratoma Presenting as an Irreducible Right Inguinal Hernia - Mithi, Mohamed Taher; Deshpande, Swanit Hemant; Mithi, Taher Abbas; Deshpande, Swarika Hemant (The Surgery Journal, 2022)
Teratomas of the ovary rarely present as inguinal hernias. Teratomas most commonly occur in the gonads or along with midline structures. Although the majority are asymptomatic, complications such as spontaneous rupture are known to occur. We present a previously unreported case of a ruptured ovarian teratoma presenting as an irreducible inguinal hernia. The patient underwent an open exploratory laparotomy with left oophorectomy, and the right inguinal hernia was repaired in the same setting with a separate inguinal incision.
Keywords: ovarian teratoma herniation; inguinal hernia; teratoma; dermoid; general surgery; onco-surgery; gynecology